2013
DOI: 10.1371/journal.pone.0066356
|View full text |Cite|
|
Sign up to set email alerts
|

Norcantharidin Inhibits Renal Interstitial Fibrosis by Blocking the Tubular Epithelial-Mesenchymal Transition

Abstract: Epithelial–mesenchymal transition (EMT) is thought to contribute to the progression of renal tubulointerstitial fibrosis. Norcantharidin (NCTD) is a promising agent for inhibiting renal interstitial fibrosis. However, the molecular mechanisms of NCTD are unclear. In this study, a unilateral ureteral obstruction (UUO) rat model was established and treated with intraperitoneal NCTD (0.1 mg/kg/day). The UUO rats treated with NCTD showed a reduction in obstruction-induced upregulation of α-SMA and downregulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…[6][7][8] In the kidney, our studies have shown that NCTD could profoundly prevent tubular EMT, inhibit the extracellular matrix (ECM) synthesis and accumulation in kidney, attenuate proteinuria and interstitial inflammation, and prevent the progression of many kinds of renal disease. [9][10][11][12] Furthermore, our clinical studies also confirmed that NCTD could reduce the proteinuria of chronic glomerular nephritis, but showed no apparently hepatorenal toxicity and bone marrow suppression (data unpublished). Mechanistically, the anti-fibrotic effect of NCTD was associated with its antagonistic effects on tubular EMT and ECM synthesis by suppressing activation of TGF-β1/Smad2/3 signaling, repressing NF-κB expression and dephosphorylation of β-catenin mediated by PP2A (data unpublished).…”
supporting
confidence: 61%
“…[6][7][8] In the kidney, our studies have shown that NCTD could profoundly prevent tubular EMT, inhibit the extracellular matrix (ECM) synthesis and accumulation in kidney, attenuate proteinuria and interstitial inflammation, and prevent the progression of many kinds of renal disease. [9][10][11][12] Furthermore, our clinical studies also confirmed that NCTD could reduce the proteinuria of chronic glomerular nephritis, but showed no apparently hepatorenal toxicity and bone marrow suppression (data unpublished). Mechanistically, the anti-fibrotic effect of NCTD was associated with its antagonistic effects on tubular EMT and ECM synthesis by suppressing activation of TGF-β1/Smad2/3 signaling, repressing NF-κB expression and dephosphorylation of β-catenin mediated by PP2A (data unpublished).…”
supporting
confidence: 61%
“…Moreover, TGF-β1 plays a predominant role in EMT process and has been recognized as a primary inducer of EMT during pulmonary fibrosis (Chen et al, 2014). Previous studies demonstrated that TGF-β1 could enhance the expression level of zinc-finger transcriptional factor Snail, which subsequently suppressed the transcription of E-cadherin (Thiery et al, 2009; Li et al, 2013). Hence, we speculated that the inhibitory effect of iPS cells on EMT in BLM-induced mice might be associated with the suppression of TGF-β1-Smad signaling activation.…”
Section: Discussionmentioning
confidence: 99%
“…CKD is known to progress to end-stage renal disease through the final common pathway of renal interstitial fibrosis [1]. Although the cellular mechanisms that facilitate tubulointerstitial fibrosis and the contribution of tubular epithelial-to-mesenchymal transition (EMT) to renal interstitial fibrosis are still controversial, tubular EMT is through to play a role in the pathogenesis of CKD [2,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%